A mechanistic approach to model the breakdown of solid food during chewing - Muhammad Syahmeer How; Jones, Jim R.; Morgenstern, Marco P.; Stuart, Eli Gray; Bronlund, John E. (Elsevier, 2022)
Chewing food prepares it for safe swallowing which, by reducing particle size and exposing new surface and blending it with saliva, benefits both digestion and the sensory experience of consumers, the latter through flavour and aroma release and textural changes. A multitude of rate processes are at play and it is the role of feed technologists to enhance their outcomes. Particle size reduction is due to subsequent selection and breakage in each chewing cycle. To develop a model based on mechanistic principles for predicting the Particle Size Distribution (PSD) of solid food bolus during chewing, it was examined which existing mathematical descriptions for selection and breakage that are most suitable for an integrated model. The application of the model is demonstrated by using peanuts as a working example.